The Relationship between CEO Characteristics and Financial Bank Performance: Empirical Evidence from Iraq - Jadah, Hamid Mohsin; Murugiah, Logasvathi; Abdul Adzis, Azira (2016)
This paper examines the link between financial bank performance and Chief Executive Officer (CEO) characteristics by the use of an unbalanced panel of 27 banks from 2005 to 2014 in lraq. This study is estimated by using the panel fixed effects approach. CEO characteristics variables are represented by CEO tenure, CEO education and CEO ownership. Return on Equity (ROE) is used to measure the bank financial performance. The findings of this study show that CEOs equipped with high qualification and high share ownership lead to better performance of Iraqi banks. However, CEO tenure has no significant impact on bank financial performance in Iraq. Collectively, the results of this study suggest that banks seeking some improvement in their financial performance should recruit CEO who has high qualification and high share ownership. This study contributes to the existing literature of the upper echelon theory and the determinants of financial banks' performance. Firstly, to the author's best knowledge, this study is considered as the first study of its kind to test effects of CEO characteristics on the financial bank performance in Iraq. Secondly, to the author's best knowledge, this study is considered as the first study of its kind to test effects of CEO education in developing countries. Thirdly, the authors attempt to classify the CEO in accordance with the educational background into two groups for comparing the effects of CEO characteristics on banks' performance. The findings of this study will till the literature gap of the association between CEO characteristics and banks' performance as demonstrated by the Upper Echelon Theory and Agency Theory.